The Influence of Village Apparatus Competence, Community Participation, Organizational Commitment, Implementation of Village Financial Information Systems on Village Fund Management Accountability - Ando, Rahbila; Soleman, Rusman; Sinen, Kasim (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The influence of village apparatus competence, community participation, organizational commitment and implementation of village financial information systems on village fund management accountability (Case Study in Galela District, North Halmahera Regency, 2023). The purpose of this study was to analyze the influence of village apparatus competence, community participation, organizational commitment and implementation of financial information systems on village fund management accountability. Methods of data collection using a questionnaire. The total sample for the study was 116 respondents in Galela sub-district, North Halmahera district in 2023. The analytical tool used was multiple linear regression using SPSS. The results showed that the competence of village apparatus, community participation did not affect the accountability of managing village funds, while organizational commitment, application of village financial information systems had an effect on accountability in managing village funds. Keywords: competence of village apparatus, community participation, organizational commitment, application of village financial information systems, accountability of village fund management.